Digital Lengthening to Treat Finger Deficiency: An Experience of 201 Digits in 104 Patients. (12th February 2017) - Ding, Zhenyu; Zhu, Xiaozhong; Fu, Kai; Zheng, Xianyou
Abstract : Objectives. We evaluated the results of digital lengthening by distraction and second-stage bone graft. Methods. We treated finger deficiency of 201 digits in 104 patients (68 males, 36 females) by digital distraction and second-stage bone graft. The distraction was performed with a rate of 1 mm/day (for the first ten days) and 0.5 mm/day followed by using a self-designed bilateral tubal-helical external fixator. The mean follow-up period was 42 months (range 6 to 60 months). Results. The mean lengthening was 29.2 mm (range 25 to 40 mm) and 18.7 mm (range 12 to 32 mm) for metacarpal bones and phalanges, respectively. The mean elongation rate was 174.4% (range 145% to 202%) and 184.8% (range 115% to 283%) for metacarpal bones and phalanges, respectively. The static two-point discriminations and SpO2 showed no significant differences before and after distraction. Four complications were observed (two skin ruptures and two phalangeal splitting). No pin tract infection or tendon rupture showed. Digital lengthening improved functions of the hand. Conclusion. Digital distraction and second-stage bone graft is an effective method to compensate disabilities caused by lack of finger length. It could be an alternative plan for patients with thumb deficiency instead of toe-to-thumb transplant and patients with finger deficiency instead of ray resection.